Response of Corn-Soybean Intercropping to Fertilizer Packages in Dry Land with Dry Climate - Kristiono, Afandi; Muzaiyanah, Siti (Universitas Muhammadiyah Yogyakarta, 2021)
Intercropping soybean with corn on dry land with dry climate (DLDC) is an alternative program to expand the soybean cultivation harvested area. This study evaluated the effectiveness of fertilization performance in the intercropping of soybean-corn in DLDC. The experiment in this study was arranged in a randomized block design, consisting of seven fertilizer package treatments with four replications. The spacing between corn (Pertiwi 3) and soybean (Dena 1) was (50 cm x 200 cm) x 40 cm (2 plants/clump) and between soybeans (Dena 1) was 40 cm x 15 cm (2-3 plants/clumps). The observations consisted of soil analysis (pH, organic matter, total N (Kjeldahl), available P, Ca-dd, Mg-dd, K-dd, and Na-dd), soybean leaf chlorophyll index (45 and 60 days after planting/dap), plant height at (45 daps and harvest), number and weight of root nodules (45 daps); Corn: chlorophyll index (56 daps), plant height (harvest), analysis of corn and soybean plant tissue (60 daps), yield, and yield components of dry seeds of soybean and corn per hectare. The results showed that effective fertilization for the intercropped crops was 53 kg N + 1,500 kg of manure per hectare in corn plant and 7 kg N + 22 kg P2O5 + 18 kg K2O + 1,500 kg/ha manure + Rhizobium Iletrisoy/Agrisoy in soybean crops.